Negative perceptions and emotional impact of striae gravidarum among pregnant women - Kaveri Karhade, MD; Megan Lawlor, MD; Heather Chubb, MS; Timothy R.B. Johnson, MD; John J. Voorhees, MD; Frank Wang, MD (Wolters Kluwer, 2021)
Background: The impact of striae gravidarum (SG), or stretch marks of pregnancy, on quality of life (QoL) is unclear. Objective: The purpose of this study was to investigate how SG affect QoL in pregnant women. Methods: In this cross-sectional survey study of healthy pregnant women who developed SG during their current pregnancy, we asked about the impact of lesions on emotional, psychological, and life-quality facets. Spearman product-moment correlation coefficients were generated to determine the strength of relationships between variables. Results: We analyzed 116 valid surveys. Participants reported permanency of SG as the top physical concern (n = 87; 75%). With regard to severity, nearly three-quarters of participants rated their lesions as very prominent (n = 24; 21%) or moderate (n = 57; 49%). Among the life-quality facets queried, embarrassment/self-consciousness was the most frequently associated with SG, with over one-third of participants reporting "a lot" (n = 19; 16%) or a "moderate" (n = 26; 22%) amount of embarrassment/self-consciousness related to having SG. Lesion severity significantly correlated with the degree of embarrassment/self-consciousness (r = .543), as well as the impact of SG on other life-quality facets, including overall QoL (r = .428), clothing choice (r = .423), self-image/self-esteem (r = .417), feelings of anxiety/depression (r = .415), and social activities (r = .313; all p ≤ .001). Nearly one-quarter of participants believed that emotional distress related to SG was similar or greater than that caused by other skin problems, such as acne, psoriasis, or eczema. Conclusion: SG can be associated with a host of negative reactions reflecting increased psychological and emotional distress, including embarrassment and decreased QoL. These consequences may compound the emotional stress of pregnancy, potentially warranting psychological support and adjustment strategies.